Influence of Late Pleistocene and Holocene climate on vegetation distributions in southwest Africa elucidated from sedimentary n-alkanes – Differences between 12°S and 20°S. (1st October 2015) - Badewien, Tanja; Vogts, Angela; Dupont, Lydie; Rullkötter, Jürgen
Abstract: Global and local climatic forcing, e.g. concentration of atmospheric CO2 or insolation, influence the distribution of C3 and C4 plants in southwest Africa. C4 plants dominate in more arid and warmer areas and are favoured by lower p CO2 levels. Several studies have assessed past and present continental vegetation by the analysis of terrestrial n -alkanes in near-coastal deep sea sediments using single samples or a small number of samples from a given climatic stage. The objectives of this study were to evaluate vegetation changes in southwest Africa with regard to climatic changes during the Late Pleistocene and the Holocene and to elucidate the potential of single sample simplifications. We analysed two sediment cores at high resolution, altogether ca. 240 samples, from the Southeast Atlantic Ocean (20°S and 12°S) covering the time spans of 18 to 1 ka and 56 to 2 ka, respectively. Our results for 20°S showed marginally decreasing C4 plant domination (of ca. 5%) during deglaciation based on average chain length (ACL27–33 values) and carbon isotopic composition of the C31 and C33 n -alkanes. Values for single samples from 18 ka and the Holocene overlap and, thus, are not significantly representative of the climatic stages they derive from. In contrast, at 12°S the n -alkane parameters show a clear difference of plant type for the Late Pleistocene (C4 plant domination, 66% C4 on average) and the Holocene (C3 plant domination, 40% C4 on average). During deglaciation vegetation change highly correlates with the increase in p CO2 (r² = 0.91). Short-term climatic events such as Heinrich Stadials or Antarctic warming periods are not reflected by vegetation changes in the catchment area. Instead, smaller vegetation fluctuations during the Late Pleistocene occur in accordance with local variations of insolation. Graphical abstract: Highlights: High resolution sediment core analyses of 18 to 9 ka (20°S) and 56 to 2 ka (12°S). C3 /C4 vegetation shift at 12°S from LGM to today, but no significant shift at 20°S. p CO2 increase highly correlates with %C4 decrease during last deglaciation. %C4 fluctuations during Late Pleistocene coincide with local insolation changes.